MINIMALISASI MISKONSEPSI KONSEP pH PADA MATERI HIDROLISIS GARAM DAN LARUTAN PENYANGGA DENGAN EKSPERIMEN BERBASIS MASALAH - Sri Haryani; Dian Listanti; Edy Cahyono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determine the application of Problem-Based Learning methods to minimizing student’s misconception on determination of pH of acidbasemixture solution. The populations of this study were XI MIPA 4, 5, and 6SMA N 1 Juwana. The sampling technique used is Purposive Random Sampling.Samples are treated differently and then followed by postest. The statistical testsused are normality test, two variance equations, hypothesis, and misconceptionlevel analysis. Average grade of experimental class postest is 75.77 and controlclass is 72.5. In the hypothesis test t292 test (2.44)> t (1.99) which means theaverage cognitive learning outcomes of the experimental class is better than thecontrol class. In the analysis of misconception level, the result of the experimental class postest experienced misconception of level 1 is 4.1% and level 2 is 3%, while the control class experienced misconception of level 1 is 17.5% and level 2 is 3.4%. Based on the results of the research can be concluded that the application of experiment-based learning problem able to minimize student misconception on salt hydrolysis and buffer solution. Keywords: experiment based problem, hydrolysis of salt, buffer solution,minimization, misconception.